PENGARUH INFLASI TERHADAP RETURN SAHAM PADA PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA (RISIKO SISTEMATIS DAN PROFITABILITAS SEBAGAI VARIABEL MEDIASI) - Geriadi, Made Ayu Desy; Wiksuana, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2017)
This study aims to determine the effect of inflation on stock returns, systematic risk and profitability as a variable mediation on property  and real estate companie s listed at the Indonesia Stock Exchange .   The population are property and real estate companies listed on the Indonesia Stock Exchange. Sample was conducted by purposive sampling method and then the number of samples are 25 companies. The research data is secondary data obtained from the website of the Indonesia Stock Exchange and the Indonesian Capital Market Directory from 2011 until 2015. Data analysis by path analysis technique with SPSS 22 software.   The results showed that: (1) inflation has a negative and significant effect on stock returns. (2) systematic risk has a positive and significant effect on stock return. (3) profitability have positive and significant effect to stock return. (4) inflation has a positive and significant effect on systematic risk (5) inflation has a positive and significant effect on profitability. Systematic risk and profitability do not mediate the effect of inflation on stock returns.